An ubiquitous based approach for Movement Coordination of Swarms of Unmanned Aerial Vehicles using mobile networks - Olivieri, Bruno; Endler, Markus (Anais do Simpósio Brasileiro de Computação Ubíqua e Pervasiva (SBCUP), 2014)
Swarms of robots have several military and civilian applications such as search and rescue missions, terrain exploration, industrial control, public security, fire combat, and several others. One of the biggest challenges of cooperative swarming in such application domains is the real-time coordination of the robot's movements in a wide-area setting, where it is expensive, or even impossible, to set up a dedicated radio communication infra-structure for the robot control. Hence, one has to resort to wide-area wireless networks. This, however, implies in a higher communication latency, which may have a significant impact on the coordination synchronicity of the swarm. In this work we tackle the swarm formation problem in wide-area settings, and propose a bandwith-efficient multi-robot coordination protocol that uses cellular 2G/3G/4G networks. This protocol has the notion of a swarm leader and is implemented on the top of an in-house developed mobile middleware with group-cast communication capability.